The acoustic emissions from single-bubble sonoluminescence - Matula, T; Hallaj, I; Cleveland, R; Crum, L; Moss, W; Roy, R (Acoustical Society of America, 1998)
Detailed measurements of the acoustic emissions from single-bubble sonoluminescence have been made utilizing both a small 200-μm aperture PVDF needle hydrophone, and a focused 10-MHz transducer. Signals obtained with the needle hydrophone show a fast (5.2 ns), probably bandlimited rise time and relatively large pulse amplitude <mtext>(≈1.7 </mtext>bar).. Below the sonoluminescence threshold, the emissions are observable, but considerably smaller in amplitude <mtext>(≈0.4 </mtext>bar).. Several signals are observed with the 10-MHz transducer and correspond to acoustic emissions from the bubble during the main collapse, as well as from the rebounds. Experiments reveal that the acoustic emissions occur at or near the minimum bubble radius. Calculations of the peak pressures and pulse widths are compared with experimental data.